The burrow – den-world Europe - Giammetti, Mariateresa (Itinerari, 2024)
Thinking of the den as a concept declined as an architectural archetype can be representative of an idea of living associated with the image of a safe, intimate and protective place. At the same time, the den can represent the starting point from which human beings are able to draw the lines of a meaningful cartography that can guide their movement in the world. The den-world expands its temenos, shifts its thresholds forward: it no longer houses just one single human being, but entire cities, pieces of continents, and whole continents. But what happens to the symbolic forms of architectural space when a den-world is forced to contract its temenos to withdraw its thresholds until it itself becomes a threshold space? The article will try to delineate the threshold places of the den-world Europe of today and the possible spatial strategies that could consolidate the architecture, understood as one of the most integral cultural techniques shaping our lives.